"If the Problem Persists, Come Back To See Me … ."—An Empirical Study of Clinical Negligence Cases Against General Practitioners. (11th October 2018) - Heywood, Rob
Abstract: The law of negligence, as it applies to General Practitioners (GPs), is underexplored in the literature. There has been no substantial research undertaken that has penetrated deeper into claims that have actually reached court in order to analyse judicial reasoning pertaining to both breach of duty and causation. Given the increased pressures that GPs now face, these are important questions to consider. It is against this backdrop that this article seeks to present the findings of an empirical investigation into a number of reported clinical negligence claims brought against GPs. This analysis provides an original contribution to the developing academic discussion surrounding the changing nature of the doctor–patient relationship, and how it has come to be viewed in the eyes of the law. It also assesses the extent to which judges have become more receptive to protecting patient rights through the law of negligence, engaging in the expanding discourse concerning judicial deference to medical decision-making. It is argued that judges should sometimes show a greater propensity to question expert medical testimony in support of GPs, because some of the issues GPs typically face are less complex than in other clinical negligence cases involving technical areas of medicine, and that causation does not appear to be such a key factor in defeating patient claims. The work also provides useful guidance for GPs and their advisers in respect of where liability is most likely to be founded and how behaviour can be modified accordingly to reduce the chances of being sued.